2010
DOI: 10.1002/asi.21391
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in search tactics during the Web‐based search process

Abstract: Although many studies have identified search tactics, few studies have explored tactic transitions. This study investigated the transitions of search tactics during the Web-based search process. Bringing their own 60 search tasks, 31 participants, representing the general public with different demographic characteristics, participated in the study. Data collected from search logs and verbal protocols were analyzed by applying both qualitative and quantitative methods. The findings of this study show that parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…They found that participants used different search tactics depending on the phase of the search session. Similar to Chen and Cooper (2002) and Xie and Joo (2010) , our proposed method identifies search tactics from logs, and we analyse user search tactics in terms of their transition patterns based on a Markov chain model. However, instead of a heuristic comparison of pattern frequencies, we summarise tactic transition patterns into a single statistics in terms of entropy rate of Markov chains, with which analysis can be performed with standard statistical tools.…”
Section: Analysis Of Tacticsmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that participants used different search tactics depending on the phase of the search session. Similar to Chen and Cooper (2002) and Xie and Joo (2010) , our proposed method identifies search tactics from logs, and we analyse user search tactics in terms of their transition patterns based on a Markov chain model. However, instead of a heuristic comparison of pattern frequencies, we summarise tactic transition patterns into a single statistics in terms of entropy rate of Markov chains, with which analysis can be performed with standard statistical tools.…”
Section: Analysis Of Tacticsmentioning
confidence: 99%
“…Further, this process allows the annotators to analyse each individual action or combination of actions in detail and in context. The drawbacks of this approach are, however: (1) similar to previous methods ( Chen & Cooper, 2002;Goodrum et al, 2003;Xie & Joo, 2010 ), it is labour intensive, although a labelling tool helps to better visualise and manipulate the sequences; (2) a strategy to resolve disagreement between annotators is needed. To address these shortcomings we explore alternative approaches, namely heuristic rule-based and statistical segmentation.…”
Section: Manual Segmentationmentioning
confidence: 99%
See 3 more Smart Citations